Calcium enhances polyplex-mediated transfection efficiency of plasmid DNA in Jurkat cells - V. S. S. Abhinav Ayyadevara; Kyung-Ho Roh (Taylor & Francis Group, 2020)
Jurkat, an immortalized cell line derived from human leukemic T lymphocytes, has been employed as an excellent surrogate model of human primary T-cells for the advancement of T-cell biology and their applications in medicine. However, presumably due to its T-cell origin, Jurkat cells are very difficult to transfect. Thus, for the genetic modification of Jurkat cells, expensive and time-consuming viral vectors are normally required. Despite many previous efforts, non-viral vectors have not yet overcome the hurdles of low transfection efficiency and/or high toxicity in transfection of Jurkat cells. Here, we report that a simple addition of calcium ions (Ca2+) into culture media at optimal concentrations can enhance the efficiency of the polyplex-mediated transfection using poly(ethylene imine) (PEI) by up to 12-fold when compared to the polyplex-only control. We show that calcium enhances the association between polyplex and Jurkat, which is at least partially responsible for the increase in transmembrane delivery of polyplex and consequential enhancement in expression of transgene. Other cations, Mg2+ or Na+ did not show similar enhancement. Interestingly, addition of Ca2+ was rather detrimental for the transfection of lipoplex on Jurkat cells. Observation of significant enhancement in the transfection of non-viral vectors with a simple and physiologically relevant reagent like Ca2+ in the engineering of hard-to-transfect cells such as Jurkat warrants further investigation on similar strategies.